Cold heaven a novel - Moore, Brian 1921-1999 (Holt, Rinehart and Winston, 1983)
Dr. Alex Davenport and his wife Marie attend a medical convention, and he is killed in a motorboat accident on their brief holiday in Nice before returning to New York. Then Alex's body, plane ticket, and passport disappear.
Keywords: Mary -- Blessed Virgin, Saint -- Apparitions and miracles -- Fiction; Religion; Near-death experiences -- Religious aspects -- Fiction; Married people -- California -- Fiction; Atheists -- California -- Fiction; California -- Fiction; Didactic fiction